The study on the development saturation profile in soil & its effect on groundwater fluctuation - Gofar, Nurly; Kassim, Khairul Anuar; Kassim, Azman; Lee, Min Lee (Faculty of Civil Engineering, 2009)
This study was carried out to investigate the mechanisms involved in the development of saturation profiles in soil. A series of numerical simulations and laboratory tests were conducted to monitor the saturation profiles in four types of soil under various rainfall conditions. In addition, two sloping sites were monitored for a period of one year to provide field verification for the findings. The understanding in saturation profile is essential to predict the shear strength of soil, particularly for slope stability problem. The study showed that the saturation profile in soil is greatly affected by the soil permeability and rainfall pattern. The effect of rainfall pattern on the saturation profile of high permeable soil is relatively insignificant. Conversely, the saturation profile in less permeable soil could be significantly altered when the soil is subjected to a prolonged rainfall. A chart is developed in the present study to determine the critical rainfall duration and intensity, as well as the resultant minimum suction value. The analysis result from the developed chart show good agreement with the field monitoring data. It is believed that the findings from the present study could lead to a better understanding of saturation profile in soil, and subsequently contribute efforts in mitigating rainfall-induced slope failure.